2017
DOI: 10.1515/njmr-2017-0003
|View full text |Cite
|
Sign up to set email alerts
|

Formal Education and New Openings For Self-Employment Amongst Foreign-Born Persons in the Swedish Healthcare Sector

Abstract: This study contributes to the discussion on the value of education for selfemployment among foreign-born persons in Sweden. The case of the deregulated healthcare sector is used to illustrate the importance of the acknowledgement of unaccustomed types of education with regards to a lack of access to the ordinary labour market and for starting a new business. Registerbased data on all individuals in Sweden with an education in healthcare are used in the analysis. The overrepresentation of foreign-born persons a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Highly educated and skilled immigrants are able to employ the 'break-through' strategy and overcome entry barriers to innovative and growing sectors, such as ICT (Baycan et al, 2012). The type of formal education affects industry choice (Urban and Schölin, 2017). Lofstrom et al (2016) found that low-skilled individuals tend to start business in highly standardized industries, while high-skilled entrepreneurs enter industries with diversified production.…”
Section: Individual Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly educated and skilled immigrants are able to employ the 'break-through' strategy and overcome entry barriers to innovative and growing sectors, such as ICT (Baycan et al, 2012). The type of formal education affects industry choice (Urban and Schölin, 2017). Lofstrom et al (2016) found that low-skilled individuals tend to start business in highly standardized industries, while high-skilled entrepreneurs enter industries with diversified production.…”
Section: Individual Characteristicsmentioning
confidence: 99%
“…Previous research has investigated particular categories of immigrant entrepreneurs such as young people (Slavnic, 2013) and second generation immigrants (Klinthäll and Urban, 2014), or immigrant entrepreneurship in specific sectors such as taxi driving (Slavnic, 2015;Slavnic and Urban, 2018) or the healthcare sector (Urban and Schölin, 2017), or the research has focused on specific groups of immigrants separately, such as refugees' entrepreneurship (Andersson, 2018) and expatriate entrepreneurs (Efendic, 2016). The groups of immigrant entrepreneurs differ significantly in terms of their motivation or access to resources in different stages of the entrepreneurial process.…”
Section: Introductionmentioning
confidence: 99%